2012
DOI: 10.1371/journal.pone.0032442
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches for Enhanced Detection of Enteroviruses from Hawaiian Environmental Waters

Abstract: Health risks associated with sewage-contaminated recreational waters are of important public health concern. Reliable water monitoring systems are therefore crucial. Current recreational water quality criteria rely predominantly on the enumeration of bacterial indicators, while potentially dangerous viral pathogens often remain undetected. Human enteric viruses have been proposed as alternative indicators; however, their detection is often hindered by low viral concentrations present in the environment. Report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 37 publications
(44 reference statements)
1
28
1
Order By: Relevance
“…Some of these viruses are more resistant to unfavorable environmental conditions and treatment processes (chlorination, UV radiation, and filtration) than bacterial and protozoa pathogens (11). Moreover, these viruses often have extremely low infectious doses (12) and can remain infective for extended period of time in environmental waters (13). It has been reported that the risk of viral infection via drinking water can be 10-to 10,000-fold higher than pathogenic bacteria at similar rates of exposure (14).…”
mentioning
confidence: 99%
“…Some of these viruses are more resistant to unfavorable environmental conditions and treatment processes (chlorination, UV radiation, and filtration) than bacterial and protozoa pathogens (11). Moreover, these viruses often have extremely low infectious doses (12) and can remain infective for extended period of time in environmental waters (13). It has been reported that the risk of viral infection via drinking water can be 10-to 10,000-fold higher than pathogenic bacteria at similar rates of exposure (14).…”
mentioning
confidence: 99%
“…Another study reported EV detection in shellfish tissue from shellfish collected from six of nine beach (66%) sites tested. In this case study, the frequency of detection of EV was higher in shellfish than in water samples from corresponding locations (Connell et al, 2012). EVs have been detected in high quality harvesting areas in Portugal with 35% of the batches analyzed showing signs of enteroviral contamination, 33% showing hepatitis A virus contamination, and 37% showing signs of NoV contamination (Mesquita et al, 2011).…”
Section: Occurrence In Shellfishmentioning
confidence: 73%
“…Aichi virus and Parechovirus) in sewage-polluted coastal waters, i.e. ENVS; (iv) molecular typing methods based on RT-PCR and nucleotide sequencing of portions of the VP1 gene (i.e., direct genotyping identification) can be used to obtain locationspecific data on enterovirus serotypes in coastal waters, which is of practical value in epidemiological surveillance and in outbreak investigation as previously mentioned; and (v) most frequently EV concentrations in marine waters are not correlated with concentrations of bacterial indicators of sewage pollution as previously documented, although the simultaneous occurrence of EVs and fecal indicator bacteria in water quality monitoring can be used in most geographical settings as a reasonable indication of recent fecal contamination and therefore of chronic pollution problems in coastal waters (Betancourt et al, 2015;Boehm et al, 2003;Connell et al, 2012;Donaldson et al, 2002;Fuhrman et al, 2005;Gersberg et al, 2006;Gregory et al, 2006;Lipp et al, 2001b;Lipp et al, 2001c;Moce-Llivina et al, 2005;Wetz et al, 2004;Wyer et al, 1995).…”
Section: Regulatory Considerations For Coastal Watersmentioning
confidence: 98%
“…Enteroviruses are associated with diverse clinical syndromes, ranging from mild febrile illness to severe central nervous system diseases, such as aseptic meningitis and encephalitis, potentially leading to paralysis (Hong et al, 2011). These viruses are faecally shed in extremely high numbers from infected individuals, and stable in the environment for extended time periods (Connell et al, 2012). They have a worldwide distribution and have previously been detected in surface water in the USA (Donaldson et al, 2002), Switzerland (Gilgen et al, 1995), Japan (Haramoto et al, 2005) and in treated drinking water in South Africa (Vivier et al, 2004).…”
Section: Introductionmentioning
confidence: 99%